A thrilling narrative of Indian captivity : dispatches from the Dakota War - Renville, Mary Butler, 1830-1895 (University of Nebraska Press, 2012)
"This edition of A Thrilling Narrative of Indian Captivity rescues from obscurity a crucially important work about the bitterly contested U.S.-Dakota War of 1862. Written by Mary Butler Renville, an Anglo woman, with the assistance of her Dakota husband, John Baptiste Renville, A Thrilling Narrative was printed only once as a book in 1863 and has not been republished since. The work details the Renvilles' experiences as 'captives' among their Dakota kin in the Upper Camp and chronicles the story of the Dakota Peace Party. Their sympathetic portrayal of those who opposed the war in 1862 combats the stereotypical view that most Dakotas supported it and illumines the injustice of their exile from Dakota homelands. From the authors' unique perspective as an interracial couple, they paint a complex picture of race, gender, and class relations on successive midwestern frontiers"--Provided by publisher.